Aerodynamics of vertical-axis wind turbine with boundary layer suction – Effects of suction momentum. (15th October 2020) - Sun, Jinjing; Sun, Xiaojing; Huang, Diangui
Abstract: Vertical axis wind turbine (VAWT) has become a research hotspot because of its structural advantages and omni-direction capability. While a further performance improvement is needed for its lower power coefficient and complex flow on blades for VAWT. Boundary layer suction (BLS) as an effective separation control method for airfoil can be a potential way to enhance the performance of VAWT. The current study first investigates boundary layer suction momentum on NACA0021 airfoil by numerical simulation. Suction momentums from 0.001 to 0.4 are investigated systematically using steady simulation with SST κ-ω turbulence model. Three zones are concluded by the corrected lift-drag ratio with suction momentum. The corrected lift-drag ratio can be increased to more than 8–14 times higher compared with the airfoil without suction within the 2°–26° angles and suction momentum within 0.02–0.2. The percentage increase in power coefficient for BLS applied on VAWT can reach to about 34.25% at the optimal tip speed ratio (TSR) for boundary layer suction VAWT at TSR = 2.33 for C μ  = 0.0075. The instantaneous power coefficient during one blade revolution and the behavior of vortex and flow structures around the suction blade are also studied to explore the physical mechanism of improving aerodynamic performance. Highlights: Suction momentums from 0 to 0.4 are studied on NACA0021 airfoil and VAWT systematically. The varying law and mechanism of aerodynamic performance of blade and VAWT with BLS is analyzed. Low drag blade with BSL can improve airfoil performance by revolutionizing the lift-drag ratio. The two-side BLS control enhances the power coefficient of VAWTs effectively.